The Breakdown Voltage Characteristics of Bamboo Insulation under Composite Layer Based - Lukmanul Hakim; T. Haryono; Suharyanto Suharyanto (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
Today, insulation system involves more than one insulation material, whether serial, parallel, or both. In insulation system, the simplest form is composite which consists of two layers of the same material. The benefit of using layered insulation is that the dielectric strength is higher than one layer with the same thickness. There are two methods to test bamboo isolator, i.e., tests of the breakdown voltage of bamboo wall and bamboo fiber. The tests used two methods of composite layers (acrylic and resin) and without composite layer (normal condition). The tests were intended to observe the breakdown voltage on each incidence in each test sample and discover the dielectric strength. The test result showed that the breakdown voltage of bamboo wall was bigger than bamboo fiber with or without composite layer. The highest dielectric strengths of acrylic layer in petung bamboo wall were 2.07 kV/mm and acrylic layer in bamboo fiber was 0.95 kV/mm in layered method. Meanwhile, in ampel bamboo wall it was 1.35 kV/mm and petung bamboo fiber it was 0.43 kV/mm in normal condition (without layer).